1994
DOI: 10.1128/iai.62.6.2508-2514.1994
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Mycobacterium bovis BCG secreting functional interleukin-2 enhances gamma interferon production by splenocytes

Abstract: Mycobacterium bovis BCG was genetically engineered to express and secrete mouse interleukin-2 (IL-2) and rat IL-2. Genes encoding IL-2 were inserted into an Escherichia coli-BCG shuttle plasmid under the control of the BCG HSP60 promoter. To facilitate study of proteins produced in this system, the IL-2 gene product was expressed (i) alone, (ii) with the mycobacterial alpha-antigen secretion signal sequence at the amino terminus, (iii) with an influenza virus hemagglutinin epitope tag at the amino terminus, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 51 publications
1
49
0
Order By: Relevance
“…MV261 BCG (BCG), a Pasteur strain transfected previously with the kanamycin resistance plasmid pMV261 [27], was used in the in vitro experiments. This strain has demonstrated the similar immunostimulatory property to that of commercial lyophilized BCG preparations.…”
Section: Bcgmentioning
confidence: 99%
“…MV261 BCG (BCG), a Pasteur strain transfected previously with the kanamycin resistance plasmid pMV261 [27], was used in the in vitro experiments. This strain has demonstrated the similar immunostimulatory property to that of commercial lyophilized BCG preparations.…”
Section: Bcgmentioning
confidence: 99%
“…Individual colonies containing pmIL-18 verified by PCR were picked and grown in Middlebrook 7H9 medium as described in Reagents . Construction of BCG Pasteur containing control vector (MV261 BCG) was described previously [39].…”
Section: Construction Of Mouse Il-18 Expression Plasmid and The Recommentioning
confidence: 99%
“…Making the BCG strain expressing the immunodominant or specific antigens, such as Ag85B [2], Ag85 complex [3], 38 kDa [4], 19 kDa [5], RD1 (region of difference 1) [6], early secreted antigenic target-6 kDa (ESAT-6) [7], and Ag85B-ESAT-6 [8], is a widely used approach. Expressing the Th1-type cytokines, namely interleukin (IL)-2 [9], IL-12 [10], granulocyte macrophage colony stimulating factors (GM-CSFs) [10], IL-18 [11], and IFN-γ [12] is the other modality. It was reported that two recombinant BCG strains expressing antigen Ag85B or RD1 resulted in enhanced protective efficacy.…”
mentioning
confidence: 99%